Modelagem matemática: o ensino de probabilidade por meio do ilusionismo - MENEZES, Adriano Araquem Baia (Universidade Federal do Oeste do Pará, 2024)
Mathematics is notably one of the subjects with the highest level of rejection by students, and there are several factors that contribute to this problem. These factors range from lack of aptitude in the area, to socioeconomic problems of the students, lack of structure of the place of study, traditionalist classes, etc. It is known, therefore, that a single pedagogical strategy cannot counteract all this complexity in the teaching process; however, the trends in Mathematics Teaching and the Ludic Resources applied to Teaching aim to reduce the gap between mathematical concepts and the students. Thus, the objective of this work is to propose, apply, and validate a Didactic Sequence (DS), associating Magic Tricks as a ludic resource and the investigative teaching processes of Mathematical Modeling. As a research methodology and data analysis, we propose the use of Didactic Engineering and its four phases, which are: 1 - preliminary analysis, 2- design and a priori analysis, 3- application of a didactic sequence and 4- a posteriori analysis and evaluation. As a result of this study, we have a Didactic Sequence using magic tricks aimed at teaching Probability, this subject being chosen due to its easy relationship with Magic Tricks. When applying the DS, we had a great participation from the students and were able to develop most of the proposed concepts in the activities, having as one of our biggest problems the application time that we used (80 minutes).